2022
DOI: 10.5897/jaerd2021.1293
|View full text |Cite
|
Sign up to set email alerts
|

Substantial factors influencing the performance of rice farmers in Mbeya Region, Tanzania

Abstract: Crops production subsector depends on various factors including natural factors as well as non-natural factors. Meanwhile, in vast areas of Tanzania including the Mbeya Region, rice farmers struggle to make their living through rice farming regardless of various challenges with which the subsector is crumbled. This study aimed at assessing the factors influencing the performance of rice farming in the Mbeya Region of Tanzania. Multi-stage sampling technique was applied to obtain representative samples. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…Based on GAM, the Edf value fitted by a single-variable including precipitation, and daily minimum temperature was greater than 1, indicating that there was a nonlinear relationship between these two climatic factors and irrigation water requirement of Rice. A more complex association between Rice and these two climatic factors has also been demonstrated in previous studies (Kulyakwave et al, 2020). The Edf value of a single variable including wind speed, photoperiod, maximum temperature, and vapor pressure deficit was 1, indicating that there was a linear relationship between these four climatic factors and the irrigation water requirement of Rice (Table 3).…”
Section: Variation In Water Requirement For Crop Irrigationsupporting
confidence: 76%
“…Based on GAM, the Edf value fitted by a single-variable including precipitation, and daily minimum temperature was greater than 1, indicating that there was a nonlinear relationship between these two climatic factors and irrigation water requirement of Rice. A more complex association between Rice and these two climatic factors has also been demonstrated in previous studies (Kulyakwave et al, 2020). The Edf value of a single variable including wind speed, photoperiod, maximum temperature, and vapor pressure deficit was 1, indicating that there was a linear relationship between these four climatic factors and the irrigation water requirement of Rice (Table 3).…”
Section: Variation In Water Requirement For Crop Irrigationsupporting
confidence: 76%
“…As a result, they produce more food on the farm than women do. The result is supported by Musaba and Mukwalikuli (2019) and David et al (2022) who reported that sex had a significant influence on rice output. The results further revealed that the coefficient of household size is also significant at 10%, which indicates that a strong and positive relationship exists between yield and household.…”
Section: Determinants Of Csa Technologies Adoption and Socioeconomic ...mentioning
confidence: 59%
“…This demonstrates a direct correlation between growing farm size and rising productivity. The results obtained by Chau and Ahamed (2022), David et al (2022), Musaba and Mukwalikuli (2019) and Kulyakwave et al (2019) indicate that land area is a primary determinant of rice yield. Farmers who have secondary occupations are 516% more likely to increase yield than those who do not engage in secondary occupations.…”
Section: Determinants Of Csa Technologies Adoption and Socioeconomic ...mentioning
confidence: 90%